Effect of Chemical Mutagens on Some Morphological Traits of Vicia faba L. Cv. Aqadulce - K.G. Al-Nuaimi, Fatima; M.J. Al-Shamma, Laith (Iraqi Journal of Science, 2023)
To investigate the effect of chemical mutagens: sodium azide (SA), hydrazine hydrate (HZ) and maleic hydrazine (MH) on morphological variations of faba bean traits. Seeds were soaked in distilled water for six hours, then in different concentrations of the above mentioned mutagens (0.01, 0.03, 0.05%) represented by (C1,C2 and C3 respectively) for six hours and planted in the field in winter 2013-2014. Factorial Experiment was arranged in Randomized Complete Block Design (RCBD) with three replications to each treatment. The results of statistical analysis showed significant differences among studied treatments. All mutagens showed significant reduction in plan height and number of branches per plant compared with control plants which gave the highest plant height and number of branches per plant (117.55cm and 13.73 respectively). SA gave a significant decrement in plant height (103.95cm). HZ gave the longest day for 50% flowering (80.78 days), a significant increase in leaf area index (4.10), chlorophyll content (43.50) have been achieved. MH caused an earliness in flowering of treated plants (79.22days). C3 was superior in the leaf area index (4.07), chlorophyll content (44.79) and earliness in flowering (78.78 days), while C1 gave a longer period of 50% flowering ( 80.89 days). Significant differences also observed in the interaction between mutagens and concentrations. (MHXC3) gave a less period to 50% flowering (77 days) and showed superiority in leaf area index (5.07) and number of branches per plant (14.79). HZ x C1 mean while an increment in number of days to50% flowering (82.66 days) but HZ x C2 gave highest plant height resulted in reached (121.18cm), while (SAxC2) treatment yielded in lowest plant height (96.49) cm and (SAxC3) gave maximum chlorophyll content (47.93).